Pengaruh Persepsi Risiko, Perilaku Keuangan, dan Pengetahuan Investasi Terhadap Keputusan Investasi pada Generasi Z di Kota Surakarta - Dewanti Tri Buana; Naili Amalia (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of risk perception, financial behavior, and investment knowledge on investment decisions among Generation Z in Surakarta City. This research employed a quantitative approach using a survey method with 75 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that risk perception, financial behavior, and investment knowledge significantly affect investment decisions. The adjusted R² value of 0.801 implies that 80,1% of the variation in investment decisions can be explained by the three independent variables, while the remaining 19,1% is influenced by other variables outside the research model. This study supports Kahneman’s Prospect Theory and the Theory of Planned Behavior, which explain that risk perception, attitudes, and knowledge shape individual investment behavior. The findings are expected to provide practical contributions for young investors, regulators, and capital market practitioners in designing financial literacy programs and effective investment strategies.